2014
DOI: 10.3390/ijms15034284
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borreliae in Archived Sera from Patients with Clinically Suspect Lyme Disease

Abstract: The diagnoses of Lyme disease based on clinical manifestations, serological findings and detection of infectious agents often contradict each other. We tested 52 blind-coded serum samples, including 20 pre-treatment and 12 post-treatment sera from clinically suspect Lyme disease patients, for the presence of residual Lyme disease infectious agents, using nested PCR amplification of a signature segment of the borrelial 16S ribosomal RNA gene for detection and direct DNA sequencing of the PCR amplicon for molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 21 publications
1
46
0
7
Order By: Relevance
“…in the general population in endemic areas (0.6-19.7%) [70][71][72][73][74][75][76]. Some studies have shown that standard serologic tests for Lyme borreliosis can fail to diagnose B. miyamotoi infections, and serology for B. miyamotoi is currently based on antibodies against the glycerophosphodiester phosphodiesterase (glpQ) gene, which is present in B. miyamotoi, but not in Lyme borreliosis spirochetes [46,77,78]. However, it is not specific for B. miyamotoi because homologs are present in other relapsing fever spirochetes [78,79].…”
Section: Seroprevalence Of Anti-borrelia Miyamotoi Antibodies In Humansmentioning
confidence: 99%
“…in the general population in endemic areas (0.6-19.7%) [70][71][72][73][74][75][76]. Some studies have shown that standard serologic tests for Lyme borreliosis can fail to diagnose B. miyamotoi infections, and serology for B. miyamotoi is currently based on antibodies against the glycerophosphodiester phosphodiesterase (glpQ) gene, which is present in B. miyamotoi, but not in Lyme borreliosis spirochetes [46,77,78]. However, it is not specific for B. miyamotoi because homologs are present in other relapsing fever spirochetes [78,79].…”
Section: Seroprevalence Of Anti-borrelia Miyamotoi Antibodies In Humansmentioning
confidence: 99%
“…In a previous report, the M1/M2 primer pair has been shown to be able to amplify a correspondent 358-bp segment of the 16S rDNA of B. coriaceae and a correspondent 358-bp segment of the 16S rDNA of a novel Borrelia, both belonging to the relapsing fever Borrelia group, as the species of B. miyamotoi [25]. …”
Section: Methodsmentioning
confidence: 99%
“…16S rRNA gene sequencing has also been successfully used to identify the etiological agents of other infections such as bacillary angiomatosis (caused by Bartonella henselae and Bartonella quintana; Regnery et al, 1992;Relman, Loutit, Schmidt, Falkow, & Tompkins, 1990) and human ehrlichiosis (caused by bacteria in the genera Ehrlichia and Anaplasma; Anderson, Dawson, Jones, & Wilson, 1991;Chen, Dumler, Bakken, & Walker, 1994;Maeda et al, 1987), which are difficult to isolate and grow in vitro. Direct PCR of the 16S rRNA gene has been used to detect borreliae in sera from patients with suspected Lyme disease (Lee, Vigliotti, Vigliotti, Jones, & Shearer, 2014), Mycoplasma and Chlamydia in patients with respiratory tract infections (Borel et al, 2008;Touati et al, 2010) and Mycobacterium species in patients with mycobacteriosis (Nakano et al, 2010;Syre, Myneedu, Arora, & Grewal, 2009). 16S rRNA gene sequencing is particularly useful for diagnosis of leprosy caused by the non-cultivable mycobacterium, Mycobacterium leprae, using skin biopsies of leprosy patients (Kurabachew, Wondimu, & Ryon, 1998;Phetsuksiri et al, 2006).…”
Section: S Rrna Gene Sequencing For Direct Detection Of Bacteria Frmentioning
confidence: 99%